Adhesion G‐protein coupled receptor 56 is required for 3T3‐L1 adipogenesis. Issue 2 (15th July 2019) - Al Hasan, Mohammad; Roy, Poornima; Dolan, Sharron; Martin, Patricia E.; Patterson, Steven; Bartholomew, Chris
Abstract: Obesity‐associated conditions represent major global health and financial burdens and understanding processes regulating adipogenesis could lead to novel intervention strategies. This study shows that adhesion G‐protein coupled receptor 56 ( GPR 56) gene transcripts are reduced in abdominal visceral white adipose tissue derived from obese Zucker rats versus lean controls. Immunostaining in 3T3‐L1 preadipocytes reveals both mitotic cell restricted surface and low level general expression patterns of Gpr56. Gpr 56 transcripts are differentially expressed in 3T3‐L1 cells during adipogenesis. Transient knockdown (KD) of Gpr 56 in 3T3‐L1 cells dramatically inhibits differentiation through reducing the accumulation of both neutral cellular lipids (56%) and production of established adipogenesis Pparγ 2 (60–80%), C/ebpα (40–78%) mediator, and Ap2 (56–80%) marker proteins. Furthermore, genome editing of Gpr 56 in 3T3‐L1 cells created CW2.2.4 and RM4.2.5.5 clones ( Gpr 56 −/− cells) with compound heterozygous deletion frameshift mutations which abolish adipogenesis. Genome edited cells have sustained levels of the adipogenesis inhibitor β‐catenin, reduced proliferation, reduced adhesion, altered profiles, and or abundance of extracellular matrix component gene transcripts for fibronectin, types I, III, and IV collagens and loss of actin stress fibers. β‐catenin KD alone is insufficient to restore adipogenesis in Gpr 56 −/− cells. Together these data show that Gpr56 is required for adipogenesis in 3T3‐L1 cells. This report is the first demonstration that Gpr56 participates in regulation of the adipogenesis developmental program. Modulation of the levels of this protein and/or its biological activity may represent a novel target for development of therapeutic agents for the treatment of obesity. Abstract : This report is the first demonstration that Gpr56 participates in regulation of the adipogenesis developmental program. Modulation of the levels of this protein and/or its biological activity may represent a novel target for development of therapeutic agents for the treatment of obesity.